Research advances of polycomb group proteins in regulating mammalian development - Li, Yan; Mo, Yanxiang; Chen, Chen; He, Jin; Guo, Zhiheng (Frontiers in Cell and Developmental Biology, 2024)
Polycomb group (PcG) proteins are a subset of epigenetic factors that are highly conserved throughout evolution. In mammals, PcG proteins can be classified into two muti-proteins complexes: Polycomb repressive complex 1 (PRC1) and PRC2.Increasing evidence has demonstrated that PcG complexes play critical roles in the regulation of gene expression, genomic imprinting, chromosome X-inactivation, and chromatin structure. Accordingly, the dysfunction of PcG proteins is tightly orchestrated with abnormal developmental processes. Here, we summarized and discussed the current knowledge of the biochemical and molecular functions of PcG complexes, especially the PRC1 and PRC2 in mammalian development including embryonic development and tissue development, which will shed further light on the deep understanding of the basic knowledge of PcGs and their functions for reproductive health and developmental disorders.